Serum matrix metalloproteinase-3 predicts radiographic joint damage and functional disability in rheumatoid arthritis - Sakthiswary Rajalingham; Omimah KJN; Endom Ismail; Shaharir SS; Sridharan Radikha (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
The search for novel biomarkers has taken centre stage in the past decades of research in Rheumatoid Arthritis (RA). The purpose of the present study was to determine the correlation of serum matrix metalloproteinase-3 (MMP-3) with disease activity, joint damage and functional disability in patients with RA. We consecutively recruited RA patients who were under follow-up at the Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Information on the RA disease characteristics were obtained from the medical records and all RA patients were assessed for DAS28 (disease activity score based on 28 joints) and Stanford Health Assessment Questionnaire (HAQ) 8-item Disability Index (HAQ-DI). The hand radiographs of the RA patients were assessed for joint damage using the Modified Sharp Score (MSS). Serum MMP-3 levels from RA patients and healthy controls were measured using the ELISA method. We recruited a total of 77 RA patients and 18 healthy controls. The serum MMP-3 levels were significantly higher among the RA patients (p<0.05). There were significant correlations between the serum MMP-3 levels and MSS (r =0.327) and HAQ-DI (r=0.256), both p<0.05. The mean serum MMP levels in RA patients with radiographic joint erosions was significantly higher than in patients without erosions (p<0.05). Likewise, the subjects with significant functional impairment i.e HAQ-DI ≥1; had significantly higher mean MMP-3 levels compared to RA patients without significant disability (p<0.05). Using multivariate analysis, HAQ-DI remained the independent predictor of serum MMP-3 in RA patients. Serum MMP-3 is a potential biomarker and predictor of radiographic joint damage and functional disability in RA.